Arterial spin labeled perfusion imaging using three‐dimensional turbo spin echo with a distributed spiral‐in/out trajectory. Issue 1 (5th March 2015) - Li, Zhiqiang; Schär, Michael; Wang, Dinghui; Zwart, Nicholas R.; Madhuranthakam, Ananth J.; Karis, John P.; Pipe, James G.
Abstract : Purpose: The three‐dimensional (3D) spiral turbo spin echo (TSE) sequence is one of the preferred readout methods for arterial spin labeled (ASL) perfusion imaging. Conventional spiral TSE collects the data using a spiral‐out readout on a stack of spirals trajectory. However, it may result in suboptimal image quality and is not flexible in protocol design. The goal of this study is to provide a more robust readout technique without such limitation. Methods: The proposed technique incorporates a spiral‐in/out readout into 3D TSE, and collects the data on a distributed spirals trajectory. The data set is split into the spiral‐in and ‐out subsets that are reconstructed separately and combined after image deblurring. Results: The volunteer results acquired with the proposed technique show no geometric distortion or signal pileup, as is present with GRASE, and no signal loss, as is seen with conventional spiral TSE. Examples also demonstrate the flexibility in changing the imaging parameters to satisfy various criteria. Conclusion: The 3D TSE with a distributed spiral‐in/out trajectory provides a robust readout technique and allows for easy protocol design, thus is a promising alternative to GRASE or conventional spiral TSE for ASL perfusion imaging. Magn Reson Med 75:266–273, 2016. © 2015 Wiley Periodicals, Inc.